CONCEALING TEXT AND EXECUTABLE FILES IN JPG FORMAT FILES WITH A STEGANOGRAPHIC COMMAND-LINE TOOL IN THE OPERATING SYSTEM KALI LINUX: CONCEALING TEXT AND EXECUTABLE FILES IN JPG FORMAT FILES WITH A STEGANOGRAPHIC COMMAND-LINE TOOL IN THE OPERATING SYSTEM KALI LINUX - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
In this scientific paper concealing text and executable files in JPG format files with a steganographic command-line tool in the Kali Linux operating system is presented. Among the myriad of steganographic tools, Steghide has gained prominence for its robust features and ease of use. Primarily focused on embedding and extracting secret messages within image files, the software tool Steghide enables users to encode text data within JPEG and BMP image formats while maintaining data integrity and minimizing visual alterations. This paper provides an in-depth examination of Steghide’s functionality, workflow, and security considerations in the context of digital steganography. It is also discussed the algorithms underpinning Steghide’s operations, its strengths, limitations and common use cases.